ByzRev 05.2023.014: Anne P. Alwis – Martin Hinterberger – Elisabeth Schiffer (eds), Metaphrasis in Byzantine Literature (Byzantioς 17).: Turnhout: Brepols 2021. - Rance, Philip (The Byzantine Review, 2023)
Anne P. Alwis – Martin Hinterberger – Elisabeth Schiffer (eds), Metaphrasis in Byzantine Literature (Byzantioς 17). Turnhout: Brepols 2021. 179 pp. – ISBN 978-2-503-59344-9 (€ 65.00)